The Importance of Characterizing the Hemoglobin Instability of New Variants: The Case of Hb Dompierre [β29(B11)Gly→Arg, HBB: c.88G>C]. (2nd January 2020) - Mondesert, Etienne; Giansily Blaizot, Muriel; Tournilhac, Olivier; Sapin, Anne François Serre; Aubin, Bernard; Pellequer, Jean-Luc; Aguilar Martinez, Patricia
Abstract: Hb Dompierre [β29(B11)Gly→Arg, HBB : c.88G>C] is a rare β-globin gene variant that was previously described in the heterozygous state in a 24-year-old female patient. It is defined in the HbVar database as being clinically and biologically asymptomatic. A few years after the first description, we had an opportunity of reassessing the index case because she presented with splenomegaly and clinical and biological manifestations of hemolysis. After ruling out the most common causes of hemolysis, further analyses on the variant hemoglobin (Hb) using brilliant cresyl blue staining, indicated that it showed mild instability, which may explain the clinical and biological manifestations. A structural bioinformatic analysis on the Hb variant suggested that the amino acid replacement may be deleterious to the integrity of the Hb. This report confirms the importance of completely characterizing all new Hb variants in order to guide the patients' clinical management and follow-up, as well as to provide the probands and their family members with appropriate genetic counseling.